Determination of Kinetic Parameters for Methane Oxidation over Pt/Î³-Al2O3 in a Fixed-Bed Reactor - Wonoputri, Vita; Effendy, Mohammad; Budhi, Yogi Wibisono; Bindar, Yazid; Subagjo, S. (Journal of Engineering and Technological Sciences, 2013)
This paper describes akinetic study for the determination of the kinetic parameters of lean methane emission oxidation over Pt/Î³-Al2O3 in a dedicated laboratory scale fixed bed reactor. A model ofthemechanistic reaction kinetic parameters has been developed. The reaction rate model was determined using therate-limiting step method, which was integrated and optimized to find the most suitable model and parameters. Based on this study, the Langmuir-Hinshelwood reaction rate model with the best correlationis the one where the rate-limiting step is thesurface reaction between methane and one adsorbed oxygen atom. The pre-exponential factor and activation energy were 9.19 x 105 and 92.04 kJ/mol, while the methane and oxygen adsorption entropy and enthalpy were â17.46 J/mol.K, â2739.36 J/mol,â16.34 J/mol.K, and â6157.09 J/mol, respectively.